2011
DOI: 10.1016/j.jchromb.2011.11.002
|View full text |Cite
|
Sign up to set email alerts
|

LC–MS/MS-based metabolites of Eurycoma longifolia (Tongkat Ali) in Malaysia (Perak and Pahang)

Abstract: A number of three LC-MS/MS hybrid systems (QTof, TripleTof and QTrap) has been used to profile small metabolites (m/z 100-1000) and to detect the targeted metabolites such as quassinoids, alkaloids, triterpene and biphenylneolignans from the aqueous extracts of Eurycoma longifolia. The metabolite profiles of small molecules showed four significant clusters in the principle component analysis for the aqueous extracts of E. longifolia, which had been collected from different geographical terrains (Perak and Paha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 30 publications
0
45
0
2
Order By: Relevance
“…It has been reported that E. longifolia contains quassinoids, triterpene, biphenylneolignan and alkaloid [7,[24][25][26]. The presence of eurycomaloactone, 14,15β-dihydroklaieanone and 13, 21-dehydroeurycomanone in E. longifolia root were identified as potent NF-κB inhibitors [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that E. longifolia contains quassinoids, triterpene, biphenylneolignan and alkaloid [7,[24][25][26]. The presence of eurycomaloactone, 14,15β-dihydroklaieanone and 13, 21-dehydroeurycomanone in E. longifolia root were identified as potent NF-κB inhibitors [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Wide spectrum of pharmacological activities of E. longifolia has been reported [2][3][4][5]. Despite wide range of traditional uses known, it is most solely for its aphrodisiac and anti-malarial properties [5][6][7]. Previous research shows that extracts from the roots of E. longifolia suppressed intracellular lipid accumulation in 3T3-L1 adipocytes, a treatment target for an anti-obesity agent [8].…”
Section: Introductionmentioning
confidence: 99%
“…Among the metabolites, quassinoids present as the highest amount. Chua et al (2011) stated more than 85 compounds have been identified from E. longifolia. Kuo et al (2004), Miyake et al (2010) and Chua et al (2011) listed known compounds that have been identified in their research and previous studies.…”
Section: Phytochemical Testmentioning
confidence: 99%
“…To detect small metabolites, high sensitivity and high mass accuracy tandem mass spectrometer is required to produce highly reliable data. Chua et al (2011) used LCMS to profile metabolites (quassinoids, alkaloids, triterpene and biphenylneolignans) of E. longifolia collected from the state of Perak and Pahang in Malaysia and extracted at different temperatures (35 and 100°C). Using three LC-MS/MS hybrid systems (QTof, TripleTof and QTrap), quassinoids particularly eurycomanone and its derivatives were detected to be at highest concentration than other metabolites.…”
Section: Phytochemical Testmentioning
confidence: 99%
See 1 more Smart Citation